Hyperspaces of closed limit sets - Lazar, A. J. (Methods of Functional Analysis and Topology, 2010)
We study Michael’s lower semifinite topology and Fell’s topology on the collection of all closed limit subsets of a topological space. Special attention is given to the subfamily of all maximal limit sets.